Papillary fibroelastoma presenting with multi-organ symptoms. Issue 6 (1st November 2020) - Kaplan, Jason G.; Kanwal, Arjun; Bahoora, Justin; Berquist, John; Hunyadi, Victor; Keirn, Richard
ABSTRACT: Papillary fibroelastomas are a rare cardiac neoplasm typically found on the left side of the heart, and most commonly on the aortic valve, which can present with cardiac or neurologic symptoms. A 51-year-old woman with no cardiac history presented to a resident clinic with complaints of left-sided facial paresthesias and palpitations for 1 month. Echocardiographic imaging showed a mass on the aortic annulus, concerning for a cardiac tumor. Due to the risk of possible embolization, if the tumor was a myxoma, the patient required intrathoracic surgery. During the intrathoracic procedure the mass was confirmed to be a papillary fibroelastoma and the patient had the mass removed without any complications. Papillary fibroelastomas are found in less than 1% of the population but can present clinically with a wide variety of symptoms. Patients with this neoplasm are at risk for severe complications, due to embolization, potentially causing cerebrovascular accidents or myocardial infarctions. We present a case of a papillary fibroelastoma producing both cardiac and neurologic symptoms.